Voicing interests and concerns: challenges for forest research - Burley, J.; Seppala, R.; El-Lakany, H.; Sayer, Jeffrey A.; Krott, M. (2001)
Forest research has to change in response to the increased interest of society in the management of forestland. The president and the vice president of IUFRO, the Assistant Director-General for Forestry in the FAO and the Past Director-General of CIFOR discuss key issues. IUFRO should become a clearing house for forest research and expertise. Research has to recognize that the culture of forestry has become a culture of conflict. More interdisciplinary and policy research should be added to the strong bio-physical sciences in forestry. It needs science to exploit the comparative advantages of local and larger-scale forest management and also needs science to bridge the gaps between the traditional and modern pools of knowledge and experience